Analisis Perubahan Tutupan Lahan di Kabupaten Muaro Jambi Menggunakan Metode Klasifikasi Random Forest - Ramadhon, Gilang; Dwi Arini; Dwi Marsiska Driptufany; Defwaldi Defwaldi; Fajrin Fajrin (Politeknik Kampar, 2025)
MuaroxJambi District is the district in Jambi Province with the largest burned area among the districts/cities affected by forest and land fires in the last eight years. The high incidence of forest and land fires will affect thexamount of land cover. The high incidence of forestxand land fires will affect the amount of land cover in the affected areas. The higher the number of forest and land fires in the area, the more the amount of land cover loss will increase. This study aims to analyze land cover changes in Muaro Jambi Regency between 2018 and 2023 usingxthe Random Forest classification algorithm on Landsat 8 OLI satellite images through the Google Earth Engine platform. Significant land use changes, such as conversion of forests and shrubs to plantations and built-up land, were observed through remote sensing-based spatial analysis.